Contribuição para a analise do tratamento dos resultados não realizados em vendas da investidora para a investida: um estudo de caso - Silva, Paulo Roberto da (1988)
The objective of this research was to analyse the intercompany gains or losses in sales of the investor from the investee in the reports of an entity shuated in Rio de Janeiro. Enfasys was imputed from the consolidation and the equity methods. In the literature review, we have focused the principal concepts linked with the study and features of the treatments considered in this research (chap. 2). We have decided to use the method of case study due the need for thoroughly identifying the effects produced by the problem focused (chap .3) . After, we have shown the case where was identify the features of the transaction, corporations and treatrrent used (chap . 4) . Next, we have apply the others treatments from the case and same appropriated comments (chaps. 5 and 6) . The results obtained have enable us to analyse the treatments applied and the it’s effects in the accounting reports (chap. 7). This done, we have come to same conclusions and suggestions for new studies on the theme researched (chap. 8).